Ectopic uterine serosal pregnancy, primary abdominal? - Tang Ploog, Luis Eduardo (2017)
The case of an ectopic pregnancy with unusual location on the uterine serosa in a patient with cornual resection after two consecutive ectopic pregnancies in that area is reported. It probably had a primary abdominal implantation without endometrial communication, and was treated with trophoblastic resection by laparoscopy.